Impact of Thyroid Dysregulation on Glycemic Control in Type 2 Diabetes Mellitus: A Comparative Investigation - Farmanullah; Rahman, Hayat Ur; Khan, Naseem; Ullah, Asad; Abbas, Waseem (Indus Journal of Bioscience Research, 2025)
Background: Diabetes mellitus (DM) and thyroid dysfunction (TD) are among the most prevalent endocrine disorders globally, with a complex bidirectional relationship. Thyroid hormones play a pivotal role in regulating carbohydrate metabolism and pancreatic function. This study investigates the prevalence and patterns of thyroid dysfunction in patients with type 2 diabetes mellitus (T2DM) compared to a non-diabetic control group. Methods: A descriptive and comparative study was conducted at Al-Sehat Hospital, Timergara, Lower Dir, involving 330 participants divided into two groups: non-diabetic controls (n=165) and confirmed T2DM patients (n=165). Blood samples were analyzed for thyroid function tests (TFTs) and glycated hemoglobin (HbA1c) using automated analyzers. Data were analyzed using SPSS version 22, with results expressed as frequencies, percentages, and descriptive statistics. Results: Thyroid dysfunction was observed in 20% of T2DM patients, significantly higher than the 8.43% in the control group. Among diabetic patients, hyperthyroidism (14.54%) was more prevalent than hypothyroidism (5.46%). Females were disproportionately affected, constituting 84.84% of diabetic cases with T2DM. Age was a significant factor, with higher T2DM prevalence in individuals over 40 years. Mean HbA1c in diabetic patients was 9.84±3.385, reflecting poor glycemic control. Conclusion: The study highlights a significantly higher prevalence of thyroid dysfunction in T2DM patients compared to non-diabetic individuals, with hyperthyroidism being the most common abnormality. Routine screening for thyroid dysfunction, particularly in high-risk groups, is essential for timely diagnosis and management to mitigate complications.